Biphasic blastoma of the lung. Report of 4 consecutive cases and evaluation of long-term prognosis - Brega-Massone, P P; Conti, B; Lequaglie, C; Cataldo, I (Minerva chirurgica, 2003)
Pulmonary blastoma is a rare malignant disease and it can occur in adults and in children. In 1952, Barnard reported the first case classified as pulmonary embryoma while in 1961 Spencer reported the first case as pulmonary blastoma. Since then 200 cases were described in literature. Four patients with adult primary pulmonary blastoma were treated in our Institute. The tumor was right sided in all cases; it belonged to upper lobe in 1 patient, to middle in 1 and to lower in 2. The patients underwent middle lobectomy in 1 case, lower lobectomy in 2 and upper lobe typical segmentectomy in one (the subject previously operated for lung adenocarcinoma). Histology detected primary pulmonary biphasic blastoma in all the cases. In only one case it was associated with hilar lymph nodal metastases. She received adjuvant chemotherapy, but after 17 months she developed distant metastases and she died 22 months after operation. About the other 3 patients: one patient died 6 months after intervention for acute cardiac disease, while two subjects are still alive and disease free 158 and 70 months after surgery. Surgical resection, when radicality could be ensured, is considered the treatment of choice, in absence of other curative therapies. The analysis of our experience confirms surgery to be a good therapeutic choice permitting to obtain long term survivals. The patient, alive ten years after the operation, is one of the longest survival case for pulmonary blastoma reported in literature.